2001
DOI: 10.1074/jbc.m007757200
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the Sensing and Transport of Phosphate and Calcium by Differentiating Chondrocytes

Abstract: During endochondral bone formation and fracture healing, cells committed to chondrogenesis undergo a temporally restricted program of differentiation that is characterized by sequential changes in their phenotype and gene expression. This results in the manufacture, remodeling, and mineralization of a cartilage template on which bone is laid down. Articular chondrocytes undergo a similar but restricted differentiation program that does not proceed to mineralization, except in pathologic conditions such as oste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 77 publications
8
61
0
Order By: Relevance
“…These observations implicate a threshold in the circulating phosphate levels, below which impairment of hypertrophic chondrocyte apoptosis is observed. Although calcium has been shown to play a role in chondrocyte differentiation (27,28), our investigations demonstrate that wild-type mice rendered hypercalcemic and hypophosphatemic by dietary means develop rickets, demonstrating that hypercalcemia cannot maintain normal growth-plate maturation in the presence of a 50% reduction in circulating phosphate levels. Therefore, our studies eliminate calcium and PTH as modulators of apoptosis.…”
Section: Discussionmentioning
confidence: 90%
“…These observations implicate a threshold in the circulating phosphate levels, below which impairment of hypertrophic chondrocyte apoptosis is observed. Although calcium has been shown to play a role in chondrocyte differentiation (27,28), our investigations demonstrate that wild-type mice rendered hypercalcemic and hypophosphatemic by dietary means develop rickets, demonstrating that hypercalcemia cannot maintain normal growth-plate maturation in the presence of a 50% reduction in circulating phosphate levels. Therefore, our studies eliminate calcium and PTH as modulators of apoptosis.…”
Section: Discussionmentioning
confidence: 90%
“…Alternatively, the capacity of TG2 to regulate Phospholipase C d1 signaling (22), and signal transduction and P i generation through GTPase and ATPase activities of TG2 (22), could modulate TG2 involvement in retinoid signaling, hypertrophy, and calcification in chondrocytes. In this regard, it is noteworthy that the accumulation of intracellular P i at critical times during chondrocyte differentiation induces mineralization and increases expression of Cbfa1 and type X collagen (54).…”
Section: Tg2 In Chondrocyte Hypertrophymentioning
confidence: 99%
“…PiT-1 plays important roles in the regulation of P i homeostasis in bone and cartilage in vitro (Cecil et al 2005;Solomon et al 2007;Sugita et al 2011;Wang et al 2005), and extracellular P i , epinephrine, insulin-like growth factor 1 and bone morphogenic protein 2 are known to regulate PiT-1 levels in osteoblast-like cells (Suzuki et al 2006;VillaBellosta et al 2009b). Moreover, it has been demonstrated that P i modulates chondrocyte differentiation (Cecil et al 2005;Fujita et al 2001;Guicheux et al 2000;Montessuit et al 1991;Wang et al 2001;Wu et al 2002) and apoptosis (Magne et al 2003;Mansfield et al 2001). Sugita et al (2011) suggested that ATP synthesis mediated by P i influx via PiT-1 is critical for the regulation of late chondrogenesis, including apoptosis and mineralization, as the differentiation of cartilage is an ATP-dependent event.…”
Section: The Role Of Transporters In Mv-mediated Initiation Of Skeletmentioning
confidence: 99%